2007
DOI: 10.1109/wmcsa.2007.4389552
|View full text |Cite
|
Sign up to set email alerts
|

User-Controllable Security and Privacy for Pervasive Computing

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
3
3
2

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 3 publications
0
18
0
Order By: Relevance
“…This article extends a previous workshop paper in which we introduced PEOPLEFINDER [5], and provides a more thorough and detailed report of our user studies.…”
Section: Introductionmentioning
confidence: 59%
“…This article extends a previous workshop paper in which we introduced PEOPLEFINDER [5], and provides a more thorough and detailed report of our user studies.…”
Section: Introductionmentioning
confidence: 59%
“…(iv) Designed Invasion (due to poorly designed features): A cell phone application that reveals location to friends, but does this without informing the user or providing control of this feature [15,16,17].…”
Section: Eai European Alliancementioning
confidence: 99%
“…Researchers found that people have significant privacy concerns when sharing their location with others [11,12,16,22,24,31,39]. Iachello et al argued that it is essential for applications to support plausible deniability when disclosing location information.…”
Section: Location Sharing Applicationsmentioning
confidence: 99%
“…Some recent applications provide users more control of their privacy preferences [39,42], such as the application mentioned by Cornwell et al [16], the later version of which is also called "Locaccino" [5]. Locaccino is a user-controllable location sharing tool which gives users control on selectively sharing their location.…”
Section: Location Sharing Applicationsmentioning
confidence: 99%